The Religious Genesis of Conspiracy Theories and Their Consequences for Democracy and Religion: The Case of QAnon - Cárcel, Roche (Religions, 2023)
Here, we will approach Conspiracy Theories (CTs) and, specifically, QAnon following the three traditional sociological fields of research. After an introduction in which we contextualise CDTs socially, culturally, economically and politically and in which we establish a conceptual map of what they mean, on the historical level (1), we will clarify their religious genesis, through the main analogies between them, magic and religion and their practices and rituals, as well as the conversion of conspiratorial agents into social agents of a religious nature. On the analytical side (2), we will deal with the QAnon belief system. Finally (3), from a critical perspective, we will describe the causes and harmful consequences of QAnon, both for religious sentiment itself and for democracy. We will conclude by pointing out that QAnon affects the coherence and stability of religious beliefs and democracy; in fact, it can be seen as libertarian authoritarianism and populism, advocating a sick freedom, the ultimate expression of the modern feeling of individual powerlessness and of a Modernity that has failed to deliver on its promises.